Resistance Realized Heritability and Fitness Cost of Cyproflanilide in Rice Stem Borer, Chilo suppressalis (Lepidoptera: Pyralidae) - Kexin Zhang; Enling Zhan; Xiaoli Chang; Eman Atef Fouad; Chunqing Zhao (Agronomy)
The rice stem borer (RSB) Chilo suppressalis is a devastating rice pest with resistance to a number of insecticides. Recently, the new meta-diamide insecticide cyproflanilide has been considered an effective insecticide to control RSB. However, its resistance risk has not been reported. In the present study, we aimed to assess the resistance risk and evaluate the fitness cost after the RSB was exposed to cyproflanilide. After five generations of selection, the resistance level of RSB increased by 1.5-fold. When h2 was 0.125, a 10-fold resistance increase in the LD50 values was expected in fourteen and thirty-one generations at the selection intensity of 90% and 50%, respectively. The selected population (RSB-SEL) had significant differences in the developmental duration of eggs, 1st, 2nd, 3rd, and 6th instar larvae, and female pupae compared to the unselected population (RSB-UNSEL). Besides, the adult longevity was shortened, and the average pupal weight of males, the emergence rate, the sex ratio, the oviposition, the mean fecundity, and the full life cycle rate were decreased in RSB-SEL. The intrinsic rate of increase (r), the net reproductive rate (R0), and the finite rate of increase (λ) of RSB-SEL were significantly lower than those of RSB-UNSEL, while the mean generation time (T) of RSB-SEL was significantly longer than that of RSB-UNSEL. Based on the results of the prediction of the generations required for a 10-fold resistance increase in the LD50, a potential risk of resistance development exists in RSB after continuous and excessive use of cyproflanilide. These results will be useful in designing the dose of cyproflanilide to control C. suppressalis in field.